The Role of the Immune System and Stem Cells in Dental Conservation - Darmadi, Eveline Yulia; Fauziah, Yessy Andriani; Adityatama, Anneke Paramita (RSF Conference Series: Business, Management and Social Sciences, 2024)
Background: Dental conservation aims to maintain teeth's appearance and functionality through various procedures. Recent advancements in stem cell research and immune system roles in tooth tissue regeneration highlight their crucial roles in oral health. The immune system is essential for healing after dental treatments and helps maintain oral health. A robust immune response can expedite the healing of damaged oral tissues and prevent further infections, enhancing the outcomes of dental conservation therapies. Purpose: This literature review examines immune system modulation and stem cell therapy in dental conservation, highlighting their potential benefits and challenges in tissue regeneration and treatment outcomes. Methodology: This review analyzes literature on the immune system and stem cell roles in dental tissue regeneration, assessing the effectiveness of immunomodulatory substances and their synergy in healing processes and tissue integration. Result: The review highlights that immunomodulatory substances effectively reduce inflammation and support regeneration, improving dental conservation outcomes. Stem cells, particularly mesenchymal stem cells from dental pulp, show promising results in clinical applications such as pulp regeneration and alveolar bone repair. The combination of immune system modulation and stem cell therapy offers superior outcomes compared to traditional methods, enhancing the quality of tissue regeneration and accelerating healing. However, challenges such as preventing adverse immune responses and ensuring proper integration of transplanted cells with host tissue remain. Ongoing research and technological advancements are expected to enhance dental conservation techniques' effectiveness and efficiency.